ESTIMASI BIAYA DENGAN MENGGUNAKAN COST SIGNIFICANT MODEL PADA PEKERJAAN PEMELIHARAAN JALAN DI KOTA BANJARBARU - Candra Yuliana; Asyifa Zuraima Ulimaz; Retna Hapsari Kertadipura (Jurnal Teknologi Berkelanjutan, 2020)
The Cost Significant Model is one of the models for estimating the total construction cost based on past construction data, which relies more on the prices that have the most influence on the total project cost as a basis for estimation, which is translated into the formulation of multiple regression. The data used are 9 work packages for road maintenance projects from 2016 to 2020 with road lengths ranging from 808 - 4,021 m and a width of 4.22 - 8.29 m. Analysis using the SPSS 20.0 application, the estimation model equation is Y= 1.042 (X7) + 0.763 (X6) + 551633,980, with a CMF of 1.11. The accuracy of the estimation results is in class 1 of the International AACE Classification which has a lower limit of -3% to -10% and an upper limit of 3% to 15%. So that the estimation model is feasible to use to check estimates and bids/tenders.